Sabtu Pagi Ceria : Senam, Kebersamaan, dan Manisnya Berbagi di Posyandu Lansia Mawar Merah RT. 11 Kelurahan Kampung Enam - Nurul Hidayat; Nur Rahmi; Rio Rio; Evi Septiana; Siti Jubaidah; Lia Bayu Natasa; Maya Nur Melisah; Yeremia Anjasmara Riyanto (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Elderly welfare has become one of the government’s concerns in creating a healthy and resilient society, particularly in tropical areas such as Tarakan City. In line with the Healthy Living Community Movement (GERMAS) initiated by the Minister of Health of the Republic of Indonesia, Budi Gunadi Sadikin, since 2020, a collaborative activity with the Mawar Merah Elderly Posyandu in Kampung 6 was carried out as a form of support for elderly health and social interaction. This activity took place on Sunday at the Posyandu yard in Kampung 6, Tarakan, North Kalimantan, involving local elderly participants in a group exercise session followed by the distribution of sweet treats as a form of togetherness. The methods used were educational, participatory, and documentative approaches. The activity aimed to improve elderly fitness, strengthen social connections, and raise awareness of the important role of the elderly in the community. Strengthening elderly health in coastal areas is part of a sustainable human development effort, in line with the policies of both the central and local governments.